Forest fire detection based on earlier pre-fire conditions using analysis hi-erarchic process (AHP) in a semi-arid climate. A case study: Belezma National Park, Algeria - Lahmar, Belkacem; Akakba, Ahmed (Acta Geographica Lodziensia, 2024)
GIS and remote sensing are the main techniques for spatial phenomena analysis, especially phenomena triggered by different factors such as fire hazards, climate change, transportation and land use. This study intends to measure forest fire vulnerability in Belezma National Park, one of Algeria's most important national parks and of high environmental value. The NDVI, NDWI and LST indices are used to evaluate the vulnerability, using satellite data obtained in the same year between May and August. The AHP is then used to integrate the suggested fire model and validated using dendrochronology and Moran's methods. The results demonstrated that vulnerability decreases relative to altitude; furthermore, the dry season is the period when most fires are triggered (timeline vulnerability factor), which was confirmed by finding out of 150–300-year-old non-burned trees in the low vulnerability area using dendrochronology method. In addition, a significant spatial correlation between elevation and vulnerability maps was found, with Moran's I score of 0.28.